When you are making plans to publish research, you need to plan for data sharing. (2nd September 2020) - Bell, R. J.; Haring, R.
Abstract: Open data is another step on the pathway of strengthening medical research. Allowing access to data facilitates testing the reproducibility of research findings. It also allows for the testing of new hypotheses, the incorporation of individual level data into meta-analyses and the development of very large data sets in which to develop and test new algorithms. There are now many data repositories that researchers can use to share their protocols, syntax and data. There are strategies both for managing what other researchers do with publically available data and for rewarding researchers who share their data. There is a strong ethical argument for making data publically available and research participants are generally supportive of this approach.